2007
DOI: 10.1016/j.physbeh.2006.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Basal testosterone moderates responses to anger faces in humans

Abstract: 41-54.]) to investigate the degree to which subjects find anger faces reinforcing. In the DILT, separate sequences of actions were paired with presentations of anger faces, neutral faces or a blank screen. After training, performance on the three sequences was measured in the absence of face stimuli. Saliva was collected for T measurement. Higher T predicted better learning on sequences paired with sub-threshold (i.e., presented too fast for conscious awareness) anger faces, suggesting that T is related to rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
78
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 64 publications
(104 reference statements)
10
78
1
1
Order By: Relevance
“…18) and women (44)(45)(46)(47). This research adds to the growing evidence that testosterone plays an important role in female social behavior (48)(49)(50)(51). In sum, the relation between testosterone and social behavior apparently has much communality in human males and females.…”
Section: Methodsmentioning
confidence: 59%
“…18) and women (44)(45)(46)(47). This research adds to the growing evidence that testosterone plays an important role in female social behavior (48)(49)(50)(51). In sum, the relation between testosterone and social behavior apparently has much communality in human males and females.…”
Section: Methodsmentioning
confidence: 59%
“…Testosterone level Testosterone level in both men and women influences selective attention to angry faces (van Honk et al, 1999;Wirth & Schultheiss, 2007). King and colleagues (2012) conducted a dot-probe task to investigate the effects of testosterone administration on attentional biases in rhesus monkeys.…”
Section: Subjectsmentioning
confidence: 99%
“…However, levels of testosterone in women vary over the course of the menstrual cycle and even over the course of several days (Sellers et al 2007). A number of studies have found associations between basal or exogenous levels of testosterone and behaviors or attitudes associated with dominance striving in men and women (Dabbs 1997, Wirth & Schultheiss 2007 and women alone (Cashdan 1995, Grant & France 2001, Hermans et al 2006a.…”
Section: Some Evidence From Adult Men and Womenmentioning
confidence: 99%